Key performance indicators in technology firms using generalized fermatean neutrosophic competition graph - Wadei Faris AL-Omeri; M Kaviyarasu; M Rajeshwari (Neutrosophic Sets and Systems)
This study investigates fermatean neutrosophic digraphs, generalized fermatean neutrosophic di-graphs, and the out-neighborhood of vertices inside generalized fermatean neutrosophic digraphs. It looks at the qualities and characteristics of generalized fermatean neutrosophic competition graphs and their matrix representations. It also establishes the minimal graph, competition number for generalized fermatean neutrosophic competition graphs, and relevant features. Finally, the paper addresses a practical implementation of these ideas.